Effects on Cognition of Stereotactic Lesional Surgery For the Treatment of Tremor in Multiple Sclerosis - Marjan Jahanshahi; Socorro Pieter; Sundus H. Alusi; Catherine R. G. Jones; Scott Glickman; John Stein; Tipu Aziz; Peter G. Bain (Behavioural Neurology)
Objective: To assess the effect of stereotactic lesional surgery for treatment of tremor in multiple sclerosis on cognition.